IoT based Green House Monitoring and Controlling System - Saud, Pradip Singh; Chand, Apil; Chaurasia, Nitesh Kumar; Aryal, Samikshya; Lamichhane, Badri Raj (IRO Journal on Sustainable Wireless Systems, 2023)
The greenhouse business is the quickest developing area around the world. The smart greenhouse helps in isolating the harvest from the climatic changes. It shelters the plant growth from immediate sunlight and outside weather conditions. To provide a monitoring and control facility within the greenhouse, a framework based on the Internet of Things will be more flexible and sensible. The research focuses on developing a smart, climate-controlled greenhouse for vegetable cultivation. This is achieved by using a low-cost, highly efficient programmable module to monitor and control the greenhouse’s climate. The boundaries of the greenhouse are adjusted based on the specific requirements for optimal harvest production. The ESP12F NodeMCU module is utilized for this purpose. The areas that require improvement include the soil’s water content, the temperature, and the moisture levels of the field. The plan involves checking with a soil sensor and a DHT11 sensor. The information gathered through the sensors are sent to the NodeMCU that is connected to the IoT or the web connection through a HTTP convention. The farmer is capable of receiving the information in his mobile phone with the help of the IoT. In the field of agriculture, innovation has rapidly advanced and continues to evolve, aiming to enhance and achieve optimal plant growth in the agricultural sector. A precise framework would undoubtedly have an impact on the world of Android/IDS smartphone applications.